ACTIVATED CARBON/PECTIN COMPOSITE ENTEROSORBENT FOR HUMAN PROTECTION FROM INTOXICATION WITH XENOBIOTICS PB(II) AND SODIUM DICLOFENAC - Jandosov, Jakpar; Alavijeh, Mo; Sultakhan, Shynggyskhan; Baimenov, Alzhan; Bernardo, Maria; Sakipova, Zuriyadda; Azat, Seytkhan; Lyubchyk, Svitlana; Zhylybayeva, Nurzhamal; Naurzbayeva, Gulmira; Mansurov, Zulkhair; Mikhalovsky, Sergey; et al. (Molecules, 2022)
The use of enterosorbents—materials which can be administered orally and eliminate toxic substances from the gastrointestinal tract (GIT) by sorption—offers an attractive complementary protection of humans against acute and chronic poisoning. In this study, we report the results of developing a microgranulated binary biomedical preparation for oral use. It was designed with a core-shell structure based on pectin with low degree of esterification as the core, and nanoporous activated carbon produced from rice husk, AC-RH, as the shell, designated as AC-RH@pectin. The adsorption properties of the synthesized materials were studied in aqueous solutions for the removal of lead (II) nitrate as a representative of toxic polyvalent metals and sodium diclofenac as an example of a medicinal drug. The composite enterosorbent demonstrated high adsorption capacity for both adsorbates studied. Adsorption kinetics of lead and diclofenac adsorption by AC-RH, pectin, and AC-RH@pectin, fitted well a pseudo-second-order model. According to the Langmuir adsorption isotherm model, the best fitted isotherm model, the maximum adsorption capacity, qmax, of AC RH@pectin for diclofenac and for lead (II) was 130.9 mg/g and 227.8 mg/g, respectively. Although qmax of AC-RH for diclofenac, 537.6 mg/g, and qmax of pectin for lead (II), 245.7 mg/g, were higher, the maximum adsorption capacity of AC-RH for lead (II), 52.7 mg/g, was much lower than that of the composite AC-RH@pectin and the adsorption capacity of pectin for diclofenac was negligible. Therefore, the composite material AC-RH@pectin demonstrated substantial efficiency of removing both species which potentially defines it as a more universal enterosorbent suitable for treating poisoning caused by substances of different chemical nature.
Keywords: Type of access: Open Access; diclofenac adsorption; lead adsorption; enterosorbent; pectin; porous carbon